Combo prospecting : the powerful one-two punch that fills your pipeline and wins sales - Hughes, Tony J. (AMACOM--American Management Association, 2018)
Unleash a killer combination of old and new sales strategies. How do you break through to impossible-to-reach executive buyers who are intent on blocking out the noise that confronts them every day? Old-school prospecting tactics or new-school techniques alone won't provide the answers. But Combo Prospecting will ... by showing how to combine time-tested sales processes with cutting-edge social media strategies and clever technology hacks. The book reveals today's new breed of Chief Executive Buyers, the channels they use, the value narrative you need, and the mix of methods that works. With actionable insights in every chapter, it explains how to: Do deep-dive research into social Locate leverage points that matter Secure decision-maker meetings Earn executive engagement Build a knockout, online brand Nurture a network that helps you thrive Profit from referrals Publish insights that set you apart and steer the agenda Employ an efficient, lethal library of scripts and templates And much, much more Want to wildly exceed your quota? Combo Prospecting is a potent playbook that will pack your pipeline and turn you into a selling champ.